2019
DOI: 10.1101/536698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tissue shape determines actin-dependent nuclear migration mechanisms in neuroepithelia

Abstract: Correct nuclear position is crucial for cellular function and tissue development.Depending on cell context however, cytoskeletal elements responsible for nuclear positioning vary. While these cytoskeletal mechanisms have been intensely studied in single cells, how nuclear positioning is linked to tissue morphology is less clear.Here, we compare apical nuclear positioning in zebrafish neuroepithelia. We find that kinetics and actin-dependent mechanisms of nuclear positioning vary in tissues of different morphol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The molecular identities of cells derived from this protocol have been extensively studied (Chambers et al, 2009, Strano et al, 2020, but we propose a minimum molecular markers panel which, to our knowledge, is unique to neuroepithelia. Of particular interest is this protocol's relatively understudied ability to induce loss of the nuclear Lamin A/C, which facilitates IKNM in vivo (Yanakieva et al, 2019b). Several other iPSC differentiation protocols have been described which produce pseudostratified cells in 3D aggregates (Lee et al, 2022, Karzbrun et al, 2021, Veenvliet et al, 2021, but direct imaging of their apical surface would not be feasible in those systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular identities of cells derived from this protocol have been extensively studied (Chambers et al, 2009, Strano et al, 2020, but we propose a minimum molecular markers panel which, to our knowledge, is unique to neuroepithelia. Of particular interest is this protocol's relatively understudied ability to induce loss of the nuclear Lamin A/C, which facilitates IKNM in vivo (Yanakieva et al, 2019b). Several other iPSC differentiation protocols have been described which produce pseudostratified cells in 3D aggregates (Lee et al, 2022, Karzbrun et al, 2021, Veenvliet et al, 2021, but direct imaging of their apical surface would not be feasible in those systems.…”
Section: Discussionmentioning
confidence: 99%
“…These displacements require nuclear deformation, which is opposed by nuclear envelope proteins such as Lamin A/C (Swift et al, 2013). Embryonic neuroepithelia characteristically lack A-type Lamin expression (Jung et al, 2012, Takamori et al, 2018, Yanakieva et al, 2019a and over-expression of Lamin A diminishes their nuclear motility during IKNM (Yanakieva et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular identities of cells derived from this protocol have been extensively studied (Chambers et al, 2009, Strano et al, 2020), but we propose a minimum molecular markers panel which, to our knowledge, is unique to neuroepithelia. Of particular interest is this protocol’s relatively understudied ability to induce loss of the nuclear Lamin A/C, which facilitates IKNM in vivo (Yanakieva et al, 2019b). Of greater consequence than their molecular identity for the studies presented here is the morphological characterisation of these iPSC-derived neuroepithelia.…”
Section: Discussionmentioning
confidence: 99%
“…Example of fluid-like behavior of nuclei upon laser ablation in the tissue (by Iskra Yanakieva 35 ). Nuclei are labelled with H2B-RFP.…”
Section: Video Legendsmentioning
confidence: 99%
“…It has been shown that in retinal neuroepithelia apical nuclear movement is driven by formin-dependent actin polymerization where actin filaments are not directly linked to the nuclear envelope 16 . Additionally, it was observed that only low levels of Lamin A/C are expressed in these retinal neuroepithelia 16,35 . We thus asked whether overexpression of Lamin A could influence nuclear deformability and mobility.…”
Section: Introductionmentioning
confidence: 99%